1996
DOI: 10.1073/pnas.93.20.11085
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor receptor associated factor 2 is a mediator of NF-kappa B activation by latent infection membrane protein 1, the Epstein-Barr virus transforming protein.

Abstract: Latent infection membrane protein 1 (LMP1), the Epstein-Barr virus transforming protein, associates with tumor necrosis factor receptor (TNFR) associated factor 1 (TRAF1) and TRAF3. Since TRAF2 has been implicated in TNFR-mediated NF-KcB activation, we have evaluated the role of TRAF2 in LMPl-mediated NF-ucB activation. TRAF2 binds in vitro to the LMP1 carboxyl-terminal cytoplasmic domain (CT), coprecipitates with LMP1 in B lymphoblasts, and relocalizes to LMP1 plasma membrane patches. A dominant negative TRAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
202
2
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(224 citation statements)
references
References 37 publications
15
202
2
5
Order By: Relevance
“…In response to HGF, the intracellular portion of the c-Met proto-oncogene receptor becomes autophosphorylated and binds to a number of proteins, including phosphatidylinositol 3-kinase, phospholipase, Cg, pp60 c-src , Grb-2, SHC, and GAB1 (Bardelli et al, 1992;Ponzetto et al, 1994;Pelicci et al, 1995). The CTAR1 domain of LMP1, which was reported to induce expression of EGFR through the TRAF signaling pathway Devergne et al, 1996;Kaye et al, 1996), was responsible for transformation of MDCK cells. However, the CTAR2 domain, which is the dominant NF-kB and JNK activating region (Huen et al, 1995;Kaye et al, 1995;Eliopoulos and Young, 1998), was not essential for transformation of MDCK cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to HGF, the intracellular portion of the c-Met proto-oncogene receptor becomes autophosphorylated and binds to a number of proteins, including phosphatidylinositol 3-kinase, phospholipase, Cg, pp60 c-src , Grb-2, SHC, and GAB1 (Bardelli et al, 1992;Ponzetto et al, 1994;Pelicci et al, 1995). The CTAR1 domain of LMP1, which was reported to induce expression of EGFR through the TRAF signaling pathway Devergne et al, 1996;Kaye et al, 1996), was responsible for transformation of MDCK cells. However, the CTAR2 domain, which is the dominant NF-kB and JNK activating region (Huen et al, 1995;Kaye et al, 1995;Eliopoulos and Young, 1998), was not essential for transformation of MDCK cells.…”
Section: Discussionmentioning
confidence: 99%
“…The distal domain located between amino acids 352 and 386 C-terminal activating region (CTAR)-2 is the dominant NF-kB and c-Jun N-terminal kinase (JNK) activating region of this protein. The proximal domain located between amino acids 187 and 231 (CTAR1) induces low levels of NF-kB and an e ect which could be attributed to its ability to interact with the TNF-a receptor associated factors (TRAFs) Kaye et al, 1996). The proximal domain (TRAF domain) also induces expression of the EGFR through a pathway distinct from NF-kB activation alone (Miller et al, 1997), and the signaling from this domain is su cient to drive initial proliferation of EBV-infected resting B lymphocytes (Kaye et al, 1995;Izumi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Also present is a VxxS sequence that was found to be important for TRAF1 and/or TRAF2 binding in CD30 and possibly TNF-R2 (Ansieau et al, 1996;Lee et al, 1996). However, it should be noted that although TRAF2 was shown to be indirectly involved in LMP1-mediated NF-kB activation from CTAR2 (Eliopoulos et al, 1997;Kaye et al, 1996), none of the TRAFs has been shown to directly bind CTAR2. Taken together, these observations suggest that signaling events from CTAR2, involving an as yet unidenti®ed protein, are qualitatively di erent to those already identi®ed for CTAR1.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, TRADD activates NF-kB through aggregation of TRAF2. Concordantly, expression of a TRADD mutant deleted of the TRAF2 association domain (TRADD residues 123 ± 293) or a dominant-negative TRAF2 mutant partially inhibits LMP1 TES2/CTAR2 activation of NF-kB (Izumi et al, 1999;Kaye et al, 1996).…”
Section: Lmp1 Activates Rel/nf-kb Through Tnf-r Associated Signaling mentioning
confidence: 99%
“…Consequently, NF-kB is released and translocates to the nucleus where it binds to its cognate sequences within the promoter/regulatory regions of many genes. The TES1/CTAR1 and TES2/CTAR2 domains of LMP1 activate NF-kB along the same pathway since overexpression of dominant-negative mutants of TRAF2, NIK, IKKa and IKKb can each inhibit LMP1-induced activation of NF-kB Kaye et al, 1996;Sylla et al, 1998).…”
Section: Lmp1 Activates Rel/nf-kb Through Tnf-r Associated Signaling mentioning
confidence: 99%